Post-traumatic stress disorder, cognitive function and adjustment problems in women burn survivors: a multicenter study - Zaqia Bano; Iram Naz (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To investigate the relationship of post-traumatic stress disorder, cognitive function and adjustment problems in women burn survivors. Methods: The analytical cross-sectional study was conducted at the Department of Psychology, University of Gujrat, Pakistan, from November 15, 2017, to July 25, 2018, and comprised women burn survivors at different burn centres of hospitals, household bases and non-governmental organisations of Lahore, Gujrat, Rawalpindi and Islamabad, Pakistan. Data was collected using the civilian version of the standardised Post-Traumatic Stress Disorder Checklist, the Montreal Cognitive Assessment and the Adjustment Problem Scale for Adults. Data was analysed using Analysis of a Moment Structures software version 21. Results: Of the 200 women, 100(50%) each were living in nuclear and joint family systems. The maximum number of women 74(37%) were aged 15-25 years; 93(46.5%) were married; and 82(41%) were employed. Post-traumatic stress disorder affected cognitive issues and adjustment of women burn survivors (p=0.000). Conclusion: Post-traumatic stress disorder significantly affected cognitive issues and adjustment problems of women burn survivors. Key Words: Post-traumatic stress disorder, Cognitive, Women burn survivors, Burn centres, Cross-sectional study, Multivariate Analysis. Continuous...